2017
DOI: 10.1186/s12955-017-0800-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, handgrip strength and falls during detraining in elderly habitual exercisers

Abstract: BackgroundThe effects of regular exercise on physical functioning and health-related quality of life (HRQOL) have been thoroughly studied. In contrast, little is known about the changes which occur following cessation of activity (detraining). Here, we have investigated the effect of a 3 month detraining period on HRQOL and on handgrip strength in elderly people who had regularly exercised, and examined the association of these variables with falls.MethodsThirty-eight women and 11 men (mean age, 75.5±5.7 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 39 publications
8
20
1
11
Order By: Relevance
“…a relative increase rate from 12 to 22 % (World Health Organization, 2018). The aging process is progressive, with intrinsic and deleterious characteristics that affect all individuals throughout life (Esain et al, 2017). Related falls and injuries are important implications of aging.…”
Section: Introductionmentioning
confidence: 99%
“…a relative increase rate from 12 to 22 % (World Health Organization, 2018). The aging process is progressive, with intrinsic and deleterious characteristics that affect all individuals throughout life (Esain et al, 2017). Related falls and injuries are important implications of aging.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent reports have consistently shown that muscular strength gains following resistance training of moderate-to-high intensity, can be maintained above baseline levels for as long as 2 to 52 weeks of detraining, in older individuals [260][261][262][263][264][265]. Specifically, Harris et al [264] noted that despite strength losses, significant levels of total-body strength were retained even after 20 weeks of detraining following an 18-week progressive RE training.…”
Section: Resistance Exercise Training and Detrainingmentioning
confidence: 99%
“…Physiological decline inherently accompanies the ageing process, affecting, among other factors, physical fitness. Consequently, falls are one of the major causes of injuries and mortality in older adults, affecting their quality of life and independence (Ahmadiahangar et al, ; Esain, Rodriguez‐Larrad, Bidaurrazaga‐Letona, & Gil, ). Frequently, falls are a consequence of the concurrence of several risk factors that can be classified as intrinsic and extrinsic factors (Pfortmueller, Lindner, & Exadaktylos, ).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, falls are a consequence of the concurrence of several risk factors that can be classified as intrinsic and extrinsic factors (Pfortmueller, Lindner, & Exadaktylos, ). Among these factors, sarcopenia, comorbidity and polypharmacy seem to increase fall risk incidence to a great extent (Ahmadiahangar et al, ; Esain et al, ; Gafner et al, ; Pfortmueller et al, ). Unfortunately, some of the consequences for older adults are physical harm, loss of self‐confidence and lack of autonomy to perform daily tasks that ultimately lead to depression and social isolation (Ahmadiahangar et al, ; Worapanwisit, Prabpai, & Rosenberg, ).…”
Section: Introductionmentioning
confidence: 99%